Forage strategies of bighorn sheep (Ovis canadensis mexicana) in northeastern Mexico - Gastelum-Mendoza, Fernando Isaac; Lozano-Cavazos, Eloy Alejandro; González-Saldívar, Fernando Noel; Uvalle-Sauceda, José Isidro; Romero-Figueroa, Guillermo; Serna-Lagunes, Ricardo; Tarango-Arámbula, Luis Antonio; Cantú-Ayala, César Martín (Ecosistemas y Recursos Agropecuarios, 2024)
Understanding the dietary needs is important for the conservation of the bighorn sheep. The objective was to identify the diet selection in Coahuila, Mexico. The research was conducted at the Rancho San Juan Wildlife Management Unit (UMA), Monclova municipality, from August 2018 to October 2019. Forage availability was assessed using 18 Canfield transects. Diet composition was estimated through microhistology on 280 fecal samples, and diet and forage diversity were assessed using the Shannon index. Cluster and principal component analyses (PCA) were applied to analyze similarity in consumption across different species and seasonal influences. Shrubs were the most available (48%). A total of 50 species and 14 families were identified in the diet, with shrubs (49.2%) and grasses (17.21%) being predominant. Tiquilia canescens, Gymnosperma glutinosum, Opuntia rufida, Medicago sativa, and Erioneuron pulchellum were the most consumed species. The bighorn sheep consumed tree and shrub species proportionally (1.1 and 1.02, respectively), preferred herbaceous plants in spring (2.24) and autumn (15.28), and grasses in spring (6.10), except in summer (0.83) when they avoided succulents. PCA revealed that the first two components explained 96.05% of the correlation between species consumption frequencies and their biological forms. Cluster analysis grouped five forage consumption categories. Conserving shrub species, which form the basis of the bighorn sheep’s diet, grasses—its preference—and succulents as buffering elements, is essential.